2009
DOI: 10.1590/s0102-76382009000500016
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia da insuficiência mitral no tratamento da insuficiência cardíaca avançada

Abstract: Rev Bras Cir Cardiovasc 2009; 24(4): 540-551

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
2
0
2
Order By: Relevance
“…Regardless of the specific etiology of heat failure, all patients with left ventricular dysfunction experience remodeling of the ventricle towards a progressive dilation [17]. Normal function of the mitral valve apparatus depends from a correct interaction among the mitral annulus, the leaflets, the sub-valvular apparatus, and the subtending myocardium [18]. It is well known that the papillary muscles are displaced as a consequence of left ventricular dilatation, creating a tension on the mitral leaflets and causing a secondary lack of coaptation.…”
Section: Mitral Regurgitation Secondary To Chronic Ischemic Cardiomyomentioning
confidence: 99%
“…Regardless of the specific etiology of heat failure, all patients with left ventricular dysfunction experience remodeling of the ventricle towards a progressive dilation [17]. Normal function of the mitral valve apparatus depends from a correct interaction among the mitral annulus, the leaflets, the sub-valvular apparatus, and the subtending myocardium [18]. It is well known that the papillary muscles are displaced as a consequence of left ventricular dilatation, creating a tension on the mitral leaflets and causing a secondary lack of coaptation.…”
Section: Mitral Regurgitation Secondary To Chronic Ischemic Cardiomyomentioning
confidence: 99%
“…The presence of mitral failure in heart failure cases is a predictive factor for worsened quality of life and mortality. 25 , 26 Several studies have demonstrated that correcting the mitral failure in patients with severe left ventricular dysfunction, either through valvuloplasty or valve replacement with preservation of the subvalvular apparatus, is associated with low mortality due to the operation, symptom relief and improved short and medium-term survival.…”
mentioning
confidence: 99%
“…O comprometimento da função cardíaca fica grave, levando a pessoa a desenvolver a insuficiência valvar mitral. Com a piora da cardiomiopatia dilatada, o coração fica cada vez mais comprometido, o que leva a uma deformação do ventrículo esquerdo (20).…”
Section: Lista De Abreviaturas E Siglasunclassified
“…A sobrecarga crônica de volume nesses pacientes traz [...] importantes adaptações cardíacas, entre elas um aumento das câmaras esquerdas e aumento da massa do ventrículo esquerdo (VE). A sobrecarga de volume tende a diminuir o relaxamento e aumentar a complacência do VE com uma função diastólica "supranormal" em corações com função ventricular preservada (20).…”
Section: Lista De Abreviaturas E Siglasunclassified